Combining gas exchange and chlorophyll a fluorescence measurements to analyze the photosynthetic activity of drip-irrigated cotton under different soil water deficits - Hong-hai LUO; Tsimilli-michael Merope; Ya-li ZHANG; Wang-feng ZHANG (Journal of Integrative Agriculture, 2016)
Gas exchange and chlorophyll a fluorescence were measured to study the effects of soil water deficit (75, 60 and 45% of field capacity, FC) on the photosynthetic activity of drip-irrigated cotton under field conditions. At light intensities above 1 200 μmol m−2 s−1, leaf net photosynthetic rate (Pn) at 60 and 45% FC was 0.75 and 0.45 times respectively than that of 75% FC. The chlorophyll content, leaf water potential and yield decreased as soil water deficit decreased. Fiber length was significantly lower at 45% FC than at 75% FC. The actual quantum yield of the photosystem II (PSII) primary photochemistry and the photochemical quenching were significantly greater at 60% FC than at 75% FC. The electron transport rate and non-photochemical quenching at 45% FC were 0.91 and 1.29 times than those at 75% FC, respectively. The amplitudes of the K- and L-bands were higher at 45% FC than at 60% FC. As soil water content decreased, active PSII reaction centers per chlorophyll decreased, functional PSII antenna size increased, and energetic connectivity between PSII units decreased. Electron flow from plastoquinol to the PSI end electron acceptors was significantly lower at 45% FC than at 75% FC. Similar to the effect on leaf Pn, water deficit reduced the performance index (PIABS, total) in the dark-adapted state. These results suggest that (i) the effect of mild water deficit on photosystem activity was mainly related to processes between plastoquinol and the PSI end electron acceptors, (ii) PSI end electron acceptors were only affected at moderate water deficit, and (iii) PIABS, total can reliably indicate the effect of water deficit on the energy supply for cotton metabolism.